TUJUAN PENDIDIKAN PERSPEKTIF AL-QURAN (TELAAH ATAS TAFSIR QS. AL-BAQARAH 2: 30 DAN QS. AL-DZĀRIYĀT 51: 56) - Muhamad Asvin Abdur Rohman; Izzuddin Rijal Fahmi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2020)
Al-Quran revealed by Lord to the Prophet Muhammad Saw. does’nt only function as a guide (hudan), but it’s a manifestation of the instructions themselves. Al-Quran is the apperance of divine words. Some of the contents of the revelation text contain stories of God’s prophetic bearers; one of them is the story of Adam’s creation which was made by God as khalifa on His earth in the form of Lord’s dialogue with His Angel. In addition, in the creation of humans, it is also intended to serve or worship the Creator. While on the other hand,–in the context of education– the purpose of education is fundamentally oriented towards the formation of religious spiritual (personal religious) as human beings who are religious and godly.